Good Governance Tools: Cross-Pollination from Nordic Corporate Law - Schøning, Lena (Arctic Review on Law and Politics, 2017)
This article aims to analyze the extent to which good governance principles applicable to Nordic companies may be an appropriate good governance tool for a public or organizational entity. The company is an advanced organizational invention for its purpose, and Nordic companies are generally regarded as highly productive and well run. Nordic companies approached as small-scale units of governance are therefore analyzed in this article as examples of the implementation of good governance principles and practices. In Nordic corporate law, a set of self-regulatory norms are a prominent part of what constitutes good corporate governance. The principles underlying these self-regulatory norms are scrutinized in this article, and the Norwegian Code of Practice for Corporate Governance is at the heart of the analysis. The norms are generally detailed and operationalized, and as such they may serve as examples of how concerns, such as accountability, transparency, predictability, conflicting interests and loyalty, clarity and equality, are put into practice. The norms also advocate value and standard setting. Although there are significant differences between the corporate sphere and the public or organizational sphere, the similarities are in many ways greater, and corporate norms may serve as good governance tools when scaled up to other issue domains or levels as done in this article.